Infection and infective endocarditis according to type of diabetes mellitus after cardiac implantable electronic device implantation: a contemporary nationwide cohort study. (3rd October 2022) - Maille, B; Bodin, A; Fauchier, G; Bisson, A; Herbert, J C; Defaye, P; Ducluzeau, P H; Deharo, J C; Fauchier, L
Abstract: Background: Patients with diabetes mellitus (DM) are at increased risk of infection. However, there are controversial reports about type 1 or 2 DM and their associations with infection and infective endocarditis (IE) following implantation of cardiac implantable electronic device (CIED). We evaluated the contemporary incidence of infections and infective endocarditis (IE) following implantation of a first-time, permanent CIED in DM patients compared to controls. Methods: This French longitudinal cohort study was based on the national hospitalization database covering hospital care from for the entire population. All adults hospitalized in French hospitals from 2010 to 2019, who underwent a de novo permanent pacemaker (PM) or implantable cardioverter defibrillator (ICD) implantation were identified together with the occurrence of post-implantation infection and IE-events during follow-up. Results: In total 688, 007 CIED patients were identified (pacemakers 87.3%, ICDs 12.7%). History of diabetes was present in 162, 490 patients: 8, 041 (1.2%) with type 1 DM and 154, 449 (22.5%) with type 2 DM. Patients with no DM were slightly older and had less prevalent associated comorbidities than those with DM. Patients with type 1 DM had less prevalent associated comorbidities than those with type 2 DM. Follow-up was 2.6±2.6 years (median 1.9, IQR 0.2–4.3 years). There were 9, 804 patients with CIED-related infection during follow-up (incidence rate 5.48 per 1000 patient.year) among whom 2, 658 had IE (incidence rate 1.49 per 1000 patient year). The incidence rate (per 1000 PYs) of CIED-related infection and IE in the different subgroups of patients with no DM, type 1 DM and type 2 DM are in Table 1. Incidence rates were higher in patients with DM than in those with no DM, and numerically higher in those with type 2 DM than in those with type 1 DM. In multivariable analysis (adjustment on baseline characteristics including age, cardiovascular and non-cardiovascular comorbidities and type of CIED), type 1 DM and type 2 DM were independent risk factors for CIED-related infection vs no DM. Type 1 DM was not associated with a statistically different risk of CIED-related infection than type 2 DM. When analysing the risk of IE during FU, type 2 DM was an independent risk factors for IE vs no DM, whilst there was a non-statistical trend for type 1 DM vs no DM. Type 1 DM was however not associated with a statistically different risk of IE than type 2 DM. Results were similar when one considered separately the periods 2010–2014 and 2015–2019 Conclusion: The risk of CIED-related infection was significantly higher in patients with type 1 and type 2 DM than in those with no DM. Although there were differences in the profile and clinical history of patients with type 1 and type 2 DM, there was no statistical difference in the risk of CIED-related infection and IE in patients with type 1 and type 2 DM in this contemporary analysis at a nationwide level. Funding Acknowledgement: Type of funding sources: None.